Candidate Species for Florida Aquaculture: American Horseshoe Crab Limulus polyphemus - Lena Donnarumma; Brittany J. Scharf; Jeffrey E. Hill; Cortney L. Ohs (EDIS)
The American horseshoe crab, Limulus polyphemus, is a member of the phylum Arthropoda, subphylum Chelicerata, and class Merostomata. Although there are four horseshoe crab species worldwide, the American horseshoe crab is primarily found in the Atlantic Ocean along the East Coast of North America. The species ranges from Maine to Mexico, but is absent between Texas in the United States and Tabasco in Mexico. They mainly inhabit estuarine areas; however, juveniles and adults can venture into the shallow oceanic environments. Embryo development occurs in the intertidal zone of sandy beaches. Sandy or muddy bottom habitats are necessary for burrowing and benthic feeding. This publication will cover their natural history, aquaculture techniques, common diseases, and their uses and markets.